Assessing climate change impacts on surface water availability using the WEAP model: a case study of the Buffalo River Catchment, South Africa - Dlamini, N.; Senzanje, A.; Mabhaudhi, Tafadzwanashe (Elsevier, 2023)
Study region: The Buffalo River (BR) catchment, KwaZulu-Natal, South Africa. Study focus: Due to the vast majority of the BR catchment’s water demands not being fully satisfied in recent years, studies investigating potential climate change impacts on the catchment’s water supply availability are needed. The study’s objective was to therefore assess climate change-induced surface water availability (SWA) variations in the BR catchment from 2020 to 2100. To achieve this, the hydrologic Water Evaluation and Planning model was forced with the catchment’s physical and hydrological data, and projected climate data from an ensemble of GCMs under RCP4.5 and RCP8.5 scenarios from CMIP5. New hydrological insights for the region: The study findings projected increased precipitation, especially in the far future (2070–2100) whereby mean annual precipitation increased by 5 % to 8286 Mm3 /annum under the worst-case climate change scenario (RCP8.5). With evapotranspiration and water abstractions averaging 4500 Mm3 /annum and 115 Mm3 /annum, respectively, surface runoff and SWA increased by 8 % and 10 %, yielding averages of 3265 Mm3 /annum and 287 Mm3 /annum, respectively. Even with the increased SWA, unmet demands also increased by 113 % towards the end of the 21st century. As the study established that climate change might exacerbate the BR catchment’s water supply system’s insufficiency to meet growing demands, such findings present an opportunity for the integrated Water-Energy-Food nexus approach to be further utilised for formulating sustainable water management strategies.